The genus Dedalopterus Sabatinelli & Pontuale, 1998 (Scarabaeidae: Melolonthinae: Leucopholini) in Laos and Vietnam, with description of a new species - Pham, Phu Van; Ahrens, Dirk; Sabatinelli, Guido (Zootaxa, 2024)
The genus Dedalopterus Sabatinelli & Pontuale, 1998 from Laos and Vietnam is reviewed: three species are present of which Dedalopterus lexuanhuei Pham, Ahrens & Sabatinelli, new species from Central Vietnam (Ngoc Linh Mts., Annamite Range) is here described. Dedalopterus malyszi Bunalski, 2001 is present in North Vietnam (Lao Cai, Hoang Lien Son Range), and Dedalopterus pulchellus Sabatinelli & Pontuale, 1998 (= D. bezdekorum Zídek & Krajčík, 2007, new synonymy) is known from Northeast Laos (Mt. Xiangkhouang and Mt. Phou Pan). Additional records, an updated checklist, and an identification key of the genus Dedalopterus are provided. All species treated are abundantly illustrated.